Design and Developing of EcoDesk Applying Sustainable Machining - Binti Izdihar, Irra Shahidah; Bin Mat Sahrin, Ahmad Izz Shauqie; Bin Nor Affifi, Muhammad Muaz Jabbar; Binti Mohd Shamsul, Nur Arisha Syamira; Ab Wahab, Norfariza; Abu Bakar, Mohd Hadzley (Engineering Science Letter, 2024)
This study aims to develop a customized study desk for children with special needs, specifically targeting primary school students from the B40 economic category in Durian Tunggal, Malaysia. The primary users, children under the age of twelve, require enhanced support and space to facilitate effective learning. The desk design will focus on improving accessibility, comfort, and practicality to accommodate diverse learning requirements, promoting inclusion and an optimal learning environment. The initiative, organized by UTeM, seeks to support financially disadvantaged families by providing affordable, tailored workstations. Additionally, the desk will be portable, ensuring ease of assembly, disassembly, and storage, thereby reducing academic burdens and fostering better student interaction.